The Effectiveness of Consumption of Dates on Increased Hemoglobin Levels in Pregnant Women with Mild Anemia at the Arrabih Primary Clinic - Miratu Megasari; Een Husanah (Science Midwifery, 2021)
Anemia in pregnant women has a negative impact on both the mother and the fetus. Possible adverse effects on pregnant women, namely the occurrence of premature birth, low birth weight babies, disability and even infant death, length of parturition due to lack of uterine propulsion(Fadlun & Feryanto, 2012). Based on the author's experience, there are still pregnant women who do not take blood-boosting tablets because the side effects of these tablets are nausea, black stools. The population in this study were all pregnant women who were recorded at the Arrabih Primary Clinic. The sample in this study was pregnant women in the first trimester who had anemia. The sampling technique used is accidental sampling. The method used in this study is a quasi-experimental. The type of design in this study was in the form of a non-equivalent design (pretest and posttest). The results of this study showed that the average hemoglobin level of pregnant women before being given dates was 9.17 gr%, while the average hemoglobin level of pregnant women after being given dates was 10.15gr%. Statistical test results value 0.To the midwives and lecturers to be able to provide more health information about the benefits of dates for increasing Hb levels in pregnant women so that the high risk of bleeding caused by anemia can be overcome.